2016
DOI: 10.4103/0972-4052.176535
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of ultraviolet stabilizers on the change in color of pigmented silicone elastomer: An in vitro study

Abstract: Aim and Objective:To compare and evaluate the effect of ultraviolet (UV) stabilizers (Chimassorb 81 and Uvinul 5050) on the color change of pigmented elastomer.Materials and Methods:Two pigments - Red (P112 Brilliant Red) and Yellow (P106 Yellow) and two UV stabilizers Chimassorb 81 and Uvinul 5050 were studied. A total of six groups of 10 samples each were fabricated using a combination of the above colors and stabilizers: Group A1 - Red control, Group A2 - Red + Chimassorb 81, Group A3 - Red + Uvinul 5050. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A stainless steel mould was prepared for the fabrication of samples as described in a previous study by Kheur et al . [ 27 ] Pigmented silicone samples rectangular in shape, of dimensions 1.5 cm × 2 cm × 0.5 cm were fabricated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A stainless steel mould was prepared for the fabrication of samples as described in a previous study by Kheur et al . [ 27 ] Pigmented silicone samples rectangular in shape, of dimensions 1.5 cm × 2 cm × 0.5 cm were fabricated.…”
Section: Methodsmentioning
confidence: 99%
“…The authors of this current study have previously analyzed the effect of UV stabilizers on the color change of pigmented silicone elastomer and observed that the addition of UV stabilizers leads to increased color stability for red and yellow pigments. [ 27 ] However, the authors noted that pigments play a vital role in degradation and color instability in elastomers and, therefore, there is a need for the development of newer pigments which would improve the color stability of the elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…According to the ISO, standard tear strength of silicone material used in current study must be 18-53 N/ mm and tensile strength 2.0-7 N/mm 2 . 10 16 Therefore, ∆E values less than equal to 3 can be considered as acceptable for evaluating color stability.…”
Section: Color Stabilitymentioning
confidence: 99%
“…These studies have focused on the effect of the incorporation of nano-oxides, ultraviolet light absorbers and opacifiers on the colour stability and mechanical properties of silicone elastomers [20–27]. Chu and Fisher [28] reported that adding 1.5% UV absorbers by weight provided adequate UV protection, which is supported by other studies [21, 24, 29]. However, colour stability remains a major problem for maxillofacial patients.…”
Section: Introductionmentioning
confidence: 98%